Ответы и объяснения

2014-02-05T14:03:09+00:00
1 вариант
1) 3а²-5а; а= -3;
    3·(-3)²-5·(-3)=3·9+15=27+15=42
2) а) -5х+3х²-9х+15х;
         3х²+х;
         х(3х+1).
    б) 3а²а-5а·3в-12ввв;
       (3а²а-5а)·(3в-12ввв);
       а(3а²-5)·3в(1-4в²);
3) 2х-3х+7х=12;
   6х=12;
   х=2
2 вариант
1) 5а²-3а;  а= -3;
   5·(-3)²-3·(-3)=5·9+9=45+9=54
2) а) -4у+7у²-5у+3у²;
       -9у+10у²;
       -у(9-10у);
   б) -4х²х-2х·3у=15уу;
      (-4х²х-2х)·(3у+15уу);
      -2х(2х²+1)·3у(1+5у).
3) -2х+3х-7х= -12;
    -6х= -12;
     х=2.